EOS parameters and elastic properties of cubic rock-salt BP - DAOUD, Salah (International Journal of Physical Research, 2019)
The present work aims to study the equation of state (EOS) under compression up to 100 GPa, and the elastic properties of cubic rocksalt Boron phosphide (BP) material. The EOS parameters and the elastic constants of our material of interest were predicted using plane wave-pseudopotential (PW-PP) approach in the framework of the density functional theory (DFT) and the density functional perturbation theory (DFPT) with the generalized gradient approximation (GGA) for the exchange-correlation functional. The Young modulus, the Poisson's ratio, the sound velocity, the Debye temperature and the melting temperature of the aggregate material were also presented. The results obtained are in general in good agreement compared to other data of the literature.